Strategi Komunikasi Pemasaran Instagram @Donatsu.Official dalam Membangun Brand Awareness Berbasis Nilai Islam - Farah Rianti Santoso; Rodliyah Khuza’i; Chairiawaty (Jurnal Riset Komunikasi Penyiaran Islam, 2025)
Abstract. This article is entitled “Marketing Communication Strategy of Instagram @donatsu.official in Building Brand Awareness Based on Islamic Values.” This study aims to understand how Donatsu implements its marketing communication strategy through Instagram to build brand awareness grounded in Islamic values. The main focus of this research is on digital marketing communication through social media, while also observing conventional strategies as supporting elements. The purpose of this research is to analyze how Donatsu conveys Islamic marketing messages to its target audience and how Islamic values are integrated into both content and service. This study uses a descriptive qualitative method with a case study approach. Data were collected through interviews, direct observation, and documentation of Donatsu’s Instagram content and offline promotional activities. The results show that Donatsu has successfully built brand awareness through a combination of digital and conventional strategies. Islamic values such as honesty (shidq), trustworthiness (amanah), politeness, and dakwah bil hikmah are consistently applied in Instagram content and direct customer service at outlets. The application of the Marketing Mix 7P theory and the AIDA model demonstrates that Donatsu’s communication is educational, persuasive, and aligned with the character of its target market, particularly families, including mothers and children. Abstrak. Artikel ini berjudul Strategi Komunikasi Pemasaran Instagram @donatsu.official dalam Membangun Brand Awareness Berbasis Nilai Islam. Artikel  bertujuan mengetahui strategi komunikasi pemasaran Donatsu melalui Instagram dalam membangun brand awareness berlandaskan nilai Islam. Fokus penelitian terletak pada komunikasi pemasaran digital melalui media sosial dengan strategi konvensional sebagai pendukung. Artikel  menganalisis penerapan strategi komunikasi pemasaran Donatsu dalam menyampaikan pesan pemasaran Islami kepada target pasar serta integrasi nilai Islam dalam konten dan pelayanan. Metode yang digunakan adalah kualitatif deskriptif dengan pendekatan studi kasus. Teknik pengumpulan data dilakukan melalui wawancara, observasi langsung, dan dokumentasi konten Instagram serta aktivitas promosi offline Donatsu. Hasil penelitian menunjukkan Donatsu berhasil membangun brand awareness melalui kombinasi strategi digital dan konvensional. Nilai Islam seperti kejujuran, amanah, kesantunan, dan dakwah bil hikmah diterapkan konsisten dalam konten Instagram maupun pelayanan di outlet. Penerapan teori Marketing Mix 7P dan model AIDA menunjukkan komunikasi Donatsu bersifat edukatif, persuasif, serta sesuai karakter target pasar keluarga terutama anak-anak dan ibu-ibu.